Gender wage discrimination in Galicia - Yolanda Pena-Boquete (European Regional Science Association (ERSA), 2005)
The wage discrimination by gender in the Galician region is one of the highest in Spain, although it presents one of the smallest wage gaps between men and women. The aim of this paper is to extend wage discrimination analysis in Galicia through two complementary theories. First, we approximate global discrimination with the Oaxaca decomposition. This method calculates the discrimination using women and men median characteristics, providing a measure based on the wage distribution average. After that, considering individual discrimination experiences, we approximate wage discrimination by using indicators based on poverty literature, as the Generalised Lorenz Inverse (discrimination curve), and the family of indexes such as Foster's, Greer's or Thorbecke's. These indexes have the property of decomposability, which allows to do an exhaustive analysis of the wage discrimination distribution in Galicia that can be the source of the differential behaviour observed at the aggregate level.
Keywords: 330